Graphene: Effects of Pb Intercalation on the Structural and Electronic Properties of Epitaxial Graphene on SiC (Small 29/2016). Issue 29 (1st August 2016) - Yurtsever, Ayhan; Onoda, Jo; Iimori, Takushi; Niki, Kohei; Miyamachi, Toshio; Abe, Masayuki; Mizuno, Seigi; Tanaka, Satoru; Komori, Fumio; Sugimoto, Yoshiaki
Abstract : On page 3956, A. Yurtsever and co‐workers demonstrate a novel method to obtain a p‐doped graphene layer on SiC (0001) substrate by Pb atom intercalation. The Pb intercalated structure is found to be stable in ambient conditions and at high temperatures up to 1250 °C. It is shown that electronic properties of graphene can be greatly tuned by Pb intercalation on SiC, which can facilitate the use of graphene in the various fields such as superconductivity and spintronics.